2017
DOI: 10.14715/cmb/2017.63.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia stimulates neural stem cell proliferation by increasing HIF"‘1α expression and activating Wnt/β-catenin signaling

Abstract: Evidence indicates that after brain injury, neurogenesis is enhanced in regions such as hippocampus, striatum, and cortex. To study the role of hypoxia-inducible factor-1 (HIF−1α) and Wnt signaling in cerebral ischemia/hypoxia-induced proliferation of neural stem cells (NSCs), we investigated the proliferation of NSCs, expression of HIF−1α, and activation of Wnt signaling under conditions of pathologic hypoxia in vitro. NSCs were isolated from 30-day-old Sprague–Dawley rats and subjected to 0.3% oxygen in a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 52 publications
2
56
0
Order By: Relevance
“…During the process of tumor evolution, Hif-1α may promote tumor cell proliferation and angiogenesis, and may cause tumor recurrence and metastasis (15). There is interactive regulation among Hif-1α and Wnt/β-catenin signalling molecules (16) and EZH2 in glioblastoma (17,18). In the present study, DZNep was used to observe the effect of DZNep on the proliferation, apoptosis, invasion and metastasis of BGC-823 gastric cancer cells, and to investigate the function of DZNep in the regulation of Hif-1α and Wnt/β-catenin signalling molecules via the inhibition of EZH2.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of tumor evolution, Hif-1α may promote tumor cell proliferation and angiogenesis, and may cause tumor recurrence and metastasis (15). There is interactive regulation among Hif-1α and Wnt/β-catenin signalling molecules (16) and EZH2 in glioblastoma (17,18). In the present study, DZNep was used to observe the effect of DZNep on the proliferation, apoptosis, invasion and metastasis of BGC-823 gastric cancer cells, and to investigate the function of DZNep in the regulation of Hif-1α and Wnt/β-catenin signalling molecules via the inhibition of EZH2.…”
Section: Introductionmentioning
confidence: 99%
“…The number of dopaminergic neuron differentiated of HIF-1α knockout mNPCs was also markedly decreased [21]. Further, over-expression of HIF-1α could stimulate NSC proliferation by activating the Wnt/β-catenin signaling pathway [22]. Increase in HIF-1α and VEGF expression promoted the proliferation and differentiation of NPCs and functional recovery following cerebral ischemia [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of LEF1 and β-catenin mRNA, nuclear mediators of wnt signaling, were also decreased following treatment with 2 mM VPA. LEF1 and β-catenin have been shown to increase cell proliferation in the developing brain of the mouse and neural stem cell [10] [11] [14]. In addition, a previous research has shown that VPA increases hsp70 protein levels in the rat cortical neurons [15].…”
Section: Discussionmentioning
confidence: 99%